PENGEMBANGAN MEDIA FRACTION AR (AUGMENTED REALITY) BERBASIS ASSEMBLR EDU PADA PEMBELAJARAN MATEMATIKA MATERI PECAHAN SEDERHANA KELAS II SD - Puspasari, Azahra Dewi; Kunti Dian Ayu Afiani; Fajar Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The objectives of this study are as follows: 1) To determine the validity of Assemblr Edu-based Fraction AR media in learning mathematics Simple Fraction material for grade II elementary school students; 2) To determine the practicality of Assemblr Edu-based Fraction AR media in learning mathematics of Simple Fractions material for grade II elementary school students; and 3) To determine the effectiveness of Assemblr Edu-based Fraction AR media in learning math material for grade II elementary school students. This research uses the ADDIE development model, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation, which is also known as development research or Research and Development (R&D). The participants in this study were students of class II-A of SDIT Ar-Rayyan. Research instruments, including validation sheets, learner and teacher response sheets, and test questions and answers, were used to collect data through questionnaires and tests. The validity, practicality, and effectiveness of Assemblr Edu-based Fraction AR media were the focus of data analysis techniques. The results of this study show that the validity is 81%, the practical media is 87% based on students' responses and 96% based on teachers' responses, and the application of Assemblr Edu-based Fraction AR media is 100% effective. In conclusion, this Assemblr Edu-based Fraction AR media development research is valid, very practical, and effective.